Systematic Literature Review: LoRa and LoraWAN projects in practice - Mochammad Haldi Widianto (Universitas Pendidikan Indonesia (UPI), 2022)
The first technology to communicate with the Wireless Sensor Network (WSN), but this technology can only perform close-range sensing and processing, in contrast to the Internet of Things (IoT) which can communicate long distances based on the Internet, while the commonly introduced assistive technology is Low-Power-Wide-Area-Network (LPWAN) which is a low power consumption technology but long range. One technology that is widely used is LoRa and its open access utilises LoRaWAN, because it has many advantages. There has been a lot of research on LoRa, LoRaWAN and surveys or reviews, but not many have focused on reviews for application rather than just testing. In this research, the author wants to conduct a review of the application of LoRa and LoRaWAN by utilising Systematic Literature Review (SLR), with the initial phase search getting 1314 and the final result is getting 45 studies taken from IEEE Explorer, ACM and Indonesian language papers (Google Scholar). Then the researcher presents a discussion related to the application of LoRa and LoRaWAN in several fields such as health, agriculture, etc.